Ethnobotany of Bedaka: Face Brightening Concoction from Sahu Tribe, West Halmahera, Indonesia - Anisatu Z. Wakhidah (Journal of Tropical Ethnobiology, 2022)
Sahu tribe at Lako Akediri village has a beauty treatment herbs concoction called bedaka that made from various plants species. Since the knowledge of making the herb is passed down by oral, it cannot be documented the whole local knowledge. Therefore, an investigation on ethnobotany of bedaka herb at Sub District Sahu, West Halmahera has been conducted. The aims of study are to inventory plant species tha used in bedaka herb; to elaborate the function of bedaka based on chemical content of used plants; and to describe conservation behaviour of community towards the used plants. Ethnobotanical data was collected by using participant observation and semi-structure interviews. The result showed that 22 species of plants from 19 families used in bedaka herbs. The most often used part is leaf (11 species) The using way of plant was by mixing the collisions of whole material, made it to sphere, and dried. The utilization of this concoction by diluted it with water. The functions of bedaka herbs are to prevent sunburn, to brighten and to soften skin face. The major resource of used plant is derived from cultivation (55%). It shows that conservation behaviour of community towards used plants has been highly enough applied. This study can be used as a reference in the development of natural-based facial beauty care products, such as skin care packages or face masks.